PENGARUH PEMBERIAN PELATIHAN TERHADAP PENGETAHUAN DAN PERILAKU CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SD INPRES MAPOLI KECAMATAN KOTA RAJA TAHUN 2022 - Stephany Rahmawati; Ribka Limbu; R. Pasifikus Christa Wijaya (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Health education is a number of experiences that have a beneficial effect on habits, knowledge and behavior related to individual health. Washing hands with soap (CTPS) is one of the sanitation measures by cleaning hands and fingers using water and soap to keep them clean. This study aims to analyze the effect of training on knowledge and behavior of handwashing with soap (CTPS) in students of SD Inpres Mapoli, Kota Raja subdistrict in 2022. This research is a type of quasi-experimental research with population in this study is 130 students. The research sample consisted of 60 students divided into an experimental group of 30 students and a control group of 30 students taken using simple random sampling. Collecting data using questionnaires and observation sheets. The data analysis used repeated measures ANOVA test. The results of this study indicate that there is a significant increase in knowledge with a large effect size (p <0.001 and partial eta squared 0.588). This training can also increase the occurrence of changes in students CTPS behavior with p < 0.001 and a large effect size (partial eta squared of 0.801). From the test results, it was found that p value < 0.05 means that H0 is rejected and H1 is accepted, which means that there is an effect of handwashing with soap training on knowledge and behavior of hand washing in elementary school children. It was concluded that in connection with this research, training on handwashing and soap should be carried out routinely in schools